Downy mildew of millets - An overview - Yuvashree, B; Johnson, I; Karthikeyan, M; Anandham, R (Plant Science Today, 2024)
Amidst global food insecurity, malnutrition, agricultural challenges, and climate change, millet farming is emerging as a viable alternativedue to its high nutritional value, resilience to extreme weather conditions, and adaptability to marginal soils. Often referred to as “super-crops”, millets gained international recognition in March 2021 during the 75th session of the United Nations General Assembly. Millets rank among the most important crops globally, following rice, wheat, maize, and sorghum. However, they are susceptible to more than fifty diseases, with the most destructive being ‘Downy Mildew’. This disease is caused by oomycete pathogens such as Sclerospora graminicola, Peronosclerospora sorghi and Sclerophthora macrospora, posing a significant threat to millet production, with yield losses ranging from 50% to 100%. This review emphasizes the importance of millet and the devastating effects of downy mildew on its yields. It explores the physiological and histological changes induced by the disease, the characterization of effector protein, and the genetic variability in millet populations. Additionally, various management techniques for combating downy mildew are examined, including chemical treatments, induced resistance, organic-based approaches, cultural practices, resistant genotypes, and advancements in nanotechnology. By compiling current knowledge on millet disease and effective management strategies, this review aims to serve as a comprehensive resource for researchers and farmers, supporting sustainable millet farming and improving global food security.